1978
DOI: 10.1111/j.1469-8749.1978.tb15302.x
|View full text |Cite
|
Sign up to set email alerts
|

Tactual Exploration by Normal Infants

Abstract: SUMMARY The age of onset for tactual exploration of the fingers, body (torso), knee, foot and penis by the fingers was determined in 100 normal infants. Exploration of the mouth, face, head, ears, nose and eyes was also studied by daily observations in the first three days of life in a second sample of 12 normal newborns, and the age of onset was recorded. The data show that the ability of the normal infant to explore by touch the various parts of his body appears to have a definite age of onset and a definite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1986
1986
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…What could determine which parts of body are known first, and which are learned later? Several authors have associated the increasing ability to recognize body parts with the progressive exposure to sensory input in the developing child as she or he explores, and learns from, the environment (Ayres, 1961; Kravitz, Goldenberg, & Neyhus, 1978; Reeves, 1985; Schilder, 1964). Some body parts are associated with extensive sensory input via tactile explorations earlier in life, which may explain why they emerge early in the children's verbal (comprehension) repertoires.…”
Section: Introductionmentioning
confidence: 99%
“…What could determine which parts of body are known first, and which are learned later? Several authors have associated the increasing ability to recognize body parts with the progressive exposure to sensory input in the developing child as she or he explores, and learns from, the environment (Ayres, 1961; Kravitz, Goldenberg, & Neyhus, 1978; Reeves, 1985; Schilder, 1964). Some body parts are associated with extensive sensory input via tactile explorations earlier in life, which may explain why they emerge early in the children's verbal (comprehension) repertoires.…”
Section: Introductionmentioning
confidence: 99%
“…Neisser (1991) demonstrated that infants acquire the self-perception first through transactions with the environment (ecological self) and others (interpersonal self), implying that self is shaped by physical and social information. Within a few weeks of birth, infants rudimentarily percept themselves by finger explosion (Kravitz et al, 1978), and be more sensitive to the information related to their own experience (Filippetti et al, 2013). With the cognitive ability maturing, infants start to recognize themselves beyond sense perception.…”
Section: Static Representation Of Others 21 Distinguish Self and Othermentioning
confidence: 99%
“…Prenatally, the functional significance of touch could be that it affords fetuses the first opportunity to learn about the areas and variations of sensitivity of their body as well as define their body limit in relation to the intrauterine environment (Kravitz, Goldenberg, & Neyhus, 1978) and potentially the extra-uterine environment as suggested by Marx & Nagy (2015). Through touch fetuses might learn a sense of self by differentiating between their own body and others, including the external environment and other bodies.…”
Section: Introductionmentioning
confidence: 99%